Overexpression of a DENND1A isoform produces a polycystic ovary syndrome theca phenotype - McAllister, Jan M. (National Academy of Sciences, 2014)
Polycystic ovary syndrome (PCOS), characterized by increased ovarian androgen biosynthesis, anovulation, and infertility, affects 5–7% of reproductive-age women. Genome-wide association studies identified PCOS candidate loci that were replicated in subsequent reports, including DENND1A, which encodes a protein associated with clathrin-coated pits where cell-surface receptors reside. However, these studies provided no information about functional roles for DENND1A in the pathogenesis of PCOS. DENND1A protein was located in the cytoplasm as well as nuclei of theca cells, suggesting a possible role in gene regulation. DENND1A immunostaining was more intense in the theca of PCOS ovaries. Using theca cells isolated and propagated from normal cycling and PCOS women, we found that DENND1A variant 2 (DENND1A.V2) protein and mRNA levels are increased in PCOS theca cells. Exosomal DENND1A.V2 RNA was significantly elevated in urine from PCOS women compared with normal cycling women. Forced overexpression of DENND1A.V2 in normal theca cells resulted in a PCOS phenotype of augmented CYP17A1 and CYP11A1 gene transcription, mRNA abundance, and androgen biosynthesis. Knock-down of DENND1A.V2 in PCOS theca cells reduced androgen biosynthesis and CYP17A1 and CYP11A1 gene transcription. An IgG specific to DENND1A.V2 also reduced androgen biosynthesis and CYP17 and CYP11A1 mRNA when added to the medium of cultured PCOS theca cells. We conclude that the PCOS candidate gene, DENND1A, plays a key role in the hyperandrogenemia associated with PCOS. These observations have both diagnostic and therapeutic implications for this common disorder.